Icon Painting as the Foundation of New Christian Imagery (on the Example of Russian ArtisticCulture in the Late 1910s and 1920s) - Balashova, Lada S. (Actual Problems of Theory and History of Art, 2017)
The author explores an almost unknown phenomenon of the 1920s — creating a new Christianart, employing a new perspective, which allows us to make an important conclusion that the new religious artwas an organic part of the culture of “new religious consciousness”. ‘Novel art’ was inspired by the darkened images of icons, which were a model of perfection in art and spirituality; paradoxically, it triggered a quest for new forms of spiritual art, the creation of individual iconic realm. The concept of vision and imprinting of the Prototype became overwhelming. The icon and avant-garde art created the foundation for new art. This essay traces the influence of avant-garde vision which discovered the meaning of iconic symbolism by formal andstylistic analysis via the process of plastic and spiritual rethinking of the iconic realm by the new art adepts. Russian religious philosophy and Goethe’s philosophy of art, adapted by Pavel Florensky, the concept of sophiology and the influence of Pavel Florensky and Fr. S. Bulgakov on artists provided the inspiration and the foundation for new artistic ideas. The sources also determined the choice of the basic instruments of art such as “Light” as a moulding and symbolic element, sophiology of colours along with symbolism and conventionalism of imagery, often by using avant-garde techniques, or by borrowing icon-like techniques from the West. The purpose of thenew Christian art was to represent our existence as an icon at all levels of creativity — from church frescoes and icons to sketches; the sanctification of human life through the iconographic depiction of gospel events.